2009
DOI: 10.1016/j.mce.2008.09.021
|View full text |Cite
|
Sign up to set email alerts
|

The stimulation of mitogenic signaling pathways by N-POMC peptides

Abstract: The N-terminal fragment of pro-opiomelancortin (POMC) has been shown previously to act as an adrenal mitogen. However, little is known about the molecular mechanisms by which mitogenesis is stimulated, although it has been shown that N-POMC1–28 stimulates the ERK pathway in human H295R cells. We have investigated signaling stimulated by N-POMC1–28 and N-POMC1–49 in the mouse Y1 cell line and found that both peptides stimulate ERK phosphorylation with maximal stimulation being achieved within 5 min. Similar res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
11
1
1
Order By: Relevance
“…We examined the anterior pituitary of the conditional KO animals and observed no differences in their development compared with the controls (data not shown). POMC, the precursor of ACTH, which is produced by the anterior pituitary, is known to stimulate proliferation of adrenocortical cells (37,38). We detected no differences in expression of Pomc at P5.…”
Section: Shh Derived From Sf1-positive Cortical Cells Stimulates Cellcontrasting
confidence: 49%
“…We examined the anterior pituitary of the conditional KO animals and observed no differences in their development compared with the controls (data not shown). POMC, the precursor of ACTH, which is produced by the anterior pituitary, is known to stimulate proliferation of adrenocortical cells (37,38). We detected no differences in expression of Pomc at P5.…”
Section: Shh Derived From Sf1-positive Cortical Cells Stimulates Cellcontrasting
confidence: 49%
“…Metabolic labelling studies and POMC fragment analysis identified that the O-linked glycosylation of Thr-45 regulated the processing of N-POMC(1–77) into N-POMC(1–49) (Bennett 1986), suggesting that stearic hindrance by the sugar moiety could prevent the processing. This has important physiological significance since the regulation of processing that this site produces, controls the level of N-POMC(1–49) and the mitogenic activity it exhibits (Pepper and Bicknell 2009). …”
Section: Processing Of Pomcmentioning
confidence: 99%
“…They also showed that in H295R cells, the peptide decreased steroid hormone production. We carried out a similar study (Pepper & Bicknell 2009) concentrating on Y1 cells and showed stimulation by both synthetic N-POMC(1-28) and purified N-POMC(1-49) resulted in an increase in phosphorylation of both ERKs 1 and 2 as well as their upstream regulators, MEK and c-RAF.…”
Section: Signaling and Intracellular Actions Of N-pomc Peptides In Thmentioning
confidence: 99%